Sensory biographies : lives and deaths among Nepal's Yolmo Buddhists - Desjarlais, Robert R. (Ethnographic studies in subjectivity ;, 2003)
Robert Desjarlais's graceful ethnography explores the life histories of two Yolmo elders, focusing on how particular sensory orientations and modalities have contributed to the making and the telling of their lives. These two are a woman in her late eighties known as Kisang Omu and a Buddhist priest in his mid-eighties known as Ghang Lama, members of an ethnically Tibetan Buddhist people whose ancestors have lived for three centuries or so along the upper ridges of the Yolmo Valley in north central Nepal.